PENGARUH DER, CR, ROA TERHADAP HARGA SAHAM PADA PERUSAHAAN DAGANG YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019-2023 - Sulastri; Inayatur Rohmah Roni; Erni Setianingrum (Journal of Research and Publication Innovation, 2025)
This study aims to analyze the effect of Debt to Equity Ratio (DER), Current Ratio (CR), and Return on Assets (ROA) on the stock prices of trading companies listed on the Indonesia Stock Exchange (IDX) during the period 2019-2023. This type of research is quantitative. The population in the study is trading companies with a sample of 6 companies for the period 2019-2023. The analysis method used is multiple linear regression analysis using the STATA program. The results of this study indicate that DER and ROA do not have a significant effect on stock prices, while CR simultaneously has a significant effect on stock prices.